On the way to the Great Depression: The demand regime of the American economy (1900-1929) - Ahmad A. Borazan (The University of Utah, Department of Economics, 2017)
This paper investigates the dynamics of income distribution, private debt, and aggregate demand in the United States in the era before the Great Depression. Based on a post-Keynesian model, I estimate the effects of the wage share and private debt on aggregate demand for private domestic output. I draw on the Post Keynesian literature to develop a framework that captures the interplay between private debt, income distribution, and demand. I use error correction model to determine the demand regime of the period. The results of the study show the demand regime was wage-led with private debt playing an important role in driving aggregate demand. Furthermore, I argue that during the roaring Twenties, higher income inequality along with the rise of destabilizing channels that propped up demand contributed to heightened economic fragility. The destabilizing channels were a real estate boom financed by mortgage debt, and a consumer spending boom financed by consumer debt. The combination of rising income inequality and higher private debt level characterized the demand regime of the Roaring Twenties which ended with the crisis of the Great Depression.
Keywords: E12; B22; E25; N10; C21; 330; income distribution; debt-led growth; wage-led growth; Great Depression